2012
DOI: 10.1016/j.fitote.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hyperglycemic action of apigenin-6-C-β-fucopyranoside from Averrhoa carambola

Abstract: A stimulatory effect of apigenin-6-C-β-fucopyranoside (1) on glucose uptake was observed when rat soleus muscle was incubated with 1, 10 and 100 μM of this flavonoid glycoside. The presence of specific insulin signaling inhibitors, such as wortmannin, an inhibitor of phosphoinositide 3-kinase (PI3K), RO318220, an inhibitor of protein kinase C (PKC), PD98059, an inhibitor of mitogen-activated protein kinase (MEK), and HNMPA(AM)₃, an insulin receptor tyrosine kinase activity inhibitor showed that apigenin-6-C-β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 29 publications
0
39
0
1
Order By: Relevance
“…Chinese herbal medicine (CHM) has been proven to protect Chinese people against disease for thousand years, which suggests that CHM may be the potent agent for further investigation. The root of Averrhoa carambola L, which is called yangtaogen in Chinese, has been reported to have many pharmacological activities, including an anti-oxidative effect and aid DM management [20,21,22]. Combined with our previous studies that have shown its hypoglycemic effect, we employed STZ-diabetic mice to investigate the molecular mechanism of EACR-mediated blood glucose reduction further.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese herbal medicine (CHM) has been proven to protect Chinese people against disease for thousand years, which suggests that CHM may be the potent agent for further investigation. The root of Averrhoa carambola L, which is called yangtaogen in Chinese, has been reported to have many pharmacological activities, including an anti-oxidative effect and aid DM management [20,21,22]. Combined with our previous studies that have shown its hypoglycemic effect, we employed STZ-diabetic mice to investigate the molecular mechanism of EACR-mediated blood glucose reduction further.…”
Section: Introductionmentioning
confidence: 99%
“…These phyto-chemicals are numerous but the important phytochemicals related to the present study are as Coumestans (wedelolactone & demethylwedelolactone) 10 , Terpenoids and their glycosides, Alkaloids 11 , Volatile oils, Saponins, Tannins, lignin 12 . Possible mechanisms for anti-hyperglycemic action of Eclipta alba based on previous studies are due to decrease intestinal absorption of glucose by α glucosidase inhibitory activity due to phytochemical, wedelolactone, demethylwedelolactone 13 , eclalbasaponin VI present in eclipta alba 14 ; Insulin secretagogue activity -volatile oil; Initiating release of insulin -tannin 15 ; Insulin sensitizing activity -saponin, tannin, lignin 15 ; Flavonoids suppress blood glucose level [16][17][18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…The crude extract at 50 mg/kg (Group IV) slightly reduced glycaemia (about 6%). In addition, the classical antihyperglycemic effect of 100 mg/kg tolbutamide (Group VI), a classical K + -ATP channels blocker [30,31], was observed at 30 and 60 min compared to the hyperglycemic group (Table 2). …”
Section: In Vivo Acute Effect Of Crude Extract Natural Triterpene 1 mentioning
confidence: 98%
“…Recrystallization using 30% ethyl acetate in hexanes afforded colorless crystals. HRMS (ESI) m/z [M + Na]+: calculated for C 30 …”
Section: Isolation Of Fern-9(11)-ene-2α3β-diolmentioning
confidence: 99%